Manajemen pemeliharaan Domba Garut tipe tangkas dan pedaging - Putrayana, Adhira Alfansa; Aulia Miftahunnisa Exa Putriyana2; Nurmeidiansyah, An An (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Garut sheep, one of Indonesia's leading livestock commodities, has two main types that are distinguished based on their rearing purpose, namely the bantam and meat types. Based on several aspects, the maintenance management between the two types of Garut sheep has quite exciting differences to be highlighted. This study aimed to evaluate the difference between the management of bantam Garut sheep and meat Garut sheep. This research used an internet-based literature study approach based on the Google Scholar, Scopus, and Mendeley application databases. The article search strategy used the keywords "Garut sheep, bantam type, meat type, maintenance system, breed, feed, housing, diseases control, and marketing". Each keyword is linked using the Boolean AND or OR operator. Furthermore, some data are tabulated and interpreted, and discussions are given according to relevant references. The results showed that based on genetic aspects, the bantam type of Garut sheep is larger than the meat type. Meanwhile, based on feed management, bantam-type Garut sheep are served feed of better quality than meat-type Garut sheep. Furthermore, based on housing management, disease control, and marketing aspects, bantam Garut sheep also receive more exclusive treatment and have a different market segment from the meat type. It can be concluded that bantam-type Garut sheep get better maintenance management and have better economic value than meat-type Garut sheep.